ITS2 rRNA Gene Sequence–Structure Phylogeny of the Chytridiomycota (Opisthokonta, Fungi) - Yuveantheni Kalaiventhan; Kensuke Seto; Matthias Wolf (Biology)
To date, standard rRNA marker genes have had limited success in resolving the phylogeny of the phylum Chytridiomycota. Whereas the conserved and easily alignable ribosomal small subunit 18S rRNA gene had problems resolving nodes relating orders, the internal transcribed spacer 2 (ITS2) has been claimed to not be alignable for this group of organisms. Although the ITS2 is a fast-evolving locus, its secondary structure is well conserved. To improve the accuracy and robustness of Chytridiomycota phylogeny, in this study, we attempt, for the first, time to reconstruct an ITS2 sequence–structure phylogeny using the primary sequence and the secondary structure information simultaneously in inferring alignments and trees. Although currently only possible for a fraction of the available data, we show a well-supported ITS2 tree for selected organisms. The results are promising for further exploration of the large number of available ITS2 sequences.